Determination Of Organizational Culture And Employee Career Development On Employee Job Satisfaction At The North Aceh Health Office - Rahmi; Muhammad Ferdiananda Chadafi; Chairul Bariah; Dina Hendiyani; Yuni Maulizar (STMIK Indonesia Banda Aceh, 2025)
The objective of this study is to investigate the influence of organizational culture and career development on employee job satisfaction at the North Aceh Health Office. This research adopts a quantitative approach utilizing a survey method. The study sample comprises 61 employees from the institution. Data were collected through a structured questionnaire that had undergone validity and reliability testing using SPSS version 29. The findings reveal that organizational culture exerts a positive and statistically significant effect on job satisfaction, as indicated by a regression coefficient of 0.363 and a t-value of 3.954, which exceeds the critical value of 1.671, with a significance level of 0.000 (p < 0.05). Furthermore, career development also demonstrates a positive and significant impact on employee job satisfaction, supported by a regression coefficient of 0.335 and a t-value of 3.041, both exceeding the required thresholds, with a significance level of 0.000 (p < 0.05).